Light Transmission through Three Types of Translucent Zirconia - Abdo Tabrizi, Maryam; Babaki, Fatemeh; Ghassemi, Amir; Najafi, Ahmad; Ekrami, Malihe (Journal of Dental School, 2019)
Objective: Zirconia cores have limited light transmittance and data are scarce on light transmission through zirconia cores with and without the veneering ceramic. Methods: In this in vitro study, Disc-shaped specimens (11.5 mm in diameter and 0.4 (0.05) mm in thickness) were fabricated of three types of zirconia namely Mamut, Heany and ZirkonZahn (n=5). A disc-shaped specimen (11.5 mm in diameter and 0.65 (0.05) mm in thickness) of veneering ceramic (Cerabien ZR, Kuraray, Noritake, Japan) was also fabricated. The intensity of light transmitted through the zirconia specimens with and without the veneering ceramic was recorded using a light curing unit (LED, SDI Radii Plus, Australia) and its respective radiometer (LED Radiometer, SDI, Australia). Data were analyzed using repeated measures ANOVA and Tukey’s HSD test. Results: A significant difference was noted in light transmission among different types of zirconia before and after veneering. After veneering, light transmission decreased in all specimens and the reduction in light transmission in Zirkonzahn group was significantly greater than that in Heany and Mamut groups (p<0.001). Conclusion: Veneered zirconia systems have limited translucency and ceramic veneering significantly decreases light transmission through zirconia.